KINERJA PERDAGANGAN INTERNASIONAL INDONESIA, 1980 -1995' - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
Although the Indonesian economy has been superbly transferredfrom being a heavily oil-dependent economy in the 1970's to a well diversified non-oil producer and exporter in the 1990s, the recent slow down of non-oil export growth, coupled with the deterioration in current account deficit in Indonesia has signalled to the policy makers, that a serious effort to improve the trade sector is a necessity. The latest data suggest that the heat is starting to come out of the economy. Nevertheless, the fact that Indonesia remains one of the highest indebted countries has made the current account deficit an even more critical sustainable development issue. This paper analyzes the changing pattern of trade and market for Indonesian products between 1980 and 1993, and its performance in 1995. The following section then analyze the trade and current account situation, compared briefly with that of Malaysia and Thailand. A major concern has been the slow down of non-oil export growth at a time when demand for non-oil imports appears to be out of control. Preliminary estimates suggest that the rate of growth of non-oil exports will remain low compared to the last three years, while non-oil import growth will be well beyond the export growth, around 30 percent annually. One of the worries has been the strength of consumer- related imports and the weakness of capital goods imports, while raw-material imports appear not to have much relation to export processing. The overall implication of such a situation is that we have to do our utmost to improve and accelerate the growth of non-oil exports while directing the non-oil imports toward more capital goods in the face of record high foreign investment agreements.